Функціональний аналіз вокально-технічних умінь майбутніх учителів музичного мистецтва з використанням герменевтичного підходу - Ван Чжибінь; Wang Zhibin (Видавництво «Код», 2025)
Резюме. У статті порушена проблема функціонального аналізу вокально-технічних умінь майбутніх учителів музичного мистецтва з використанням герменевтичного підходу. Визначено, що в умовах сьогодення зростає потреба в переосмисленні змісту та структури вокально-технічної підготовки майбутніх учителів музичного мистецтва з використанням герменевтичного підходу, який акцентує на процесах розуміння та інтерпретації музичного тексту від пізнання мистецьких явищ до їх ціннісного осмислення. З урахуванням того, що вокальна підготовка майбутніх учителів музичного мистецтва є інтегрованим процесом, який поєднує вокально-виконавську, аналітичну, методичну, педагогічну діяльність, виокремлено такі ключові функції: світоглядно-пізнавальна, конструктивна та інтерактивна.

Abstract. The article raises the problem of functional analysis of vocal-technical skills of future teachers of music using a hermeneutic approach. It is determined that in today's conditions there is a growing need to rethink the content and structure of vocal-technical training of future teachers of music using a hermeneutic approach, which emphasizes the processes of understanding and interpreting a musical text from the knowledge of artistic phenomena to their value comprehension. Taking into account the fact that vocal training of future teachers of music is an integrated process that combines vocal-performing, analytical, methodological, pedagogical activities, the following key functions are distinguished: ideological-cognitive, constructive and interactive. It is revealed that the ideological and cognitive function provides a deep understanding of the musical text, its cultural, figurative and semantic layers, contributing to the awareness of singing technique not only as a mechanical process, but as an interpretative reproduction of artistic meaning. The constructive function determines the logic of building vocal and technical training, contributes to the selection of work methods, structuring educational tasks in a combination of technical actions with the emotional and figurative content of the work. The interactive function ensures dialogicity and co-creation in the process of vocal training, creates conditions for a joint search for meanings and collective analysis of musical texts, which contributes to a deeper understanding of technical techniques in the context of an artistic idea. It is proven that a complex combination of the identified functions allows us to consider singing technique not only as a set of physiological or acoustic skills, but as a dynamic system of meanings, which is formed in the interaction of the singer with musical material, cultural context and his own vocal and performing experience.
Functional analysis of vocal-technical skills of future music teachers using a hermeneutic approach
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: вокально-технічні вміння; герменевтичний підхід; аналіз; світогляднопізнавальна; конструктивна та інтерактивна функції; майбутній вчитель музичного мистецтва; вокальне навчання